Bioconcentration and Bioaccumulation 0f Chromium Heavy Metal in Small-Sclae Catfish Farming Ponds - Rara, Augita Tri Clara Shostakovich Datu (Al-Hayat: Journal of Biology and Applied Biology, 2023)
Pollution of the Opak River by heavy metals such as chromium can have an impact on the use of river water for aquaculture in the Bantul Regency area. This study aims to determine the level of concentration of chromium contamination in water samples, sediments and their accumulation in catfish cultivated by the community. The method in this study in taking samples of sediment, water, and catfish is in the form of a cluster random sampling method. Chromium level analysis using AAS (Atomic Adsorption Spectrophotometer) instrumentation-based tests. The results of this reaseacrh show that chromium pollutants from the Opak river have been dispersed into fish farming ponds through irrigation canals. Chromium concentrations in water, sediments, and catfish with ranges and averages respectively of 0.113-0.144 mg/L, 0.667-1.281 mg/L, and 0.258-0.434 mg/L.